SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA BERPRESTASI DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (Studi Kasus Di SMKN 1 Bawen) - Putri, Sherly Pradipta Arshyindi; Andika, Robby; Priyadi, Priyadi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
The selection of scholarship candidates at SMK N 1 Bawen is still carried out manually using computers, making it vulnerable to data input errors and inconsistencies in the calculation of criteria scores. Furthermore, the lack of a fair and scientific assessment method often leads to social jealousy among students and their guardians. Manual management of selection information also makes it difficult to manage user access rights as needed. This study aims to develop a web-based information management system that applies the Simple Additive Weighting (SAW) method to improve the accuracy of calculating criteria scores for scholarship candidates automatically and fairly. This system is designed to be able to manage user access rights easily and securely. The research methodology used includes needs analysis, system design, implementation, and testing. The results show that the developed system can reduce data input errors, improve calculation consistency, and provide more transparent and systematic decisions. The implementation of this system is expected to assist schools in managing scholarship recipient selection more effectively and efficiently.